Grow rich and clean up later? International assistance and the provision of environmental quality in low- and middle-income countries - Gabi Ruoff (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
This paper deals with the question whether low- and middle-income countries that are politically better integrated into the international system are able to provide higher levels of environmental quality than could be expected only according to their national income levels. Using time-series cross-section regression analysis of 110 countries for the period 1950-1999 it can be shown that those countries that have signed and ratified more environmental treaties, have significantly lower SO2 emissions than countries that are less integrated into the international system. However, in contrast to theoretical predictions democratic low- and middle-income countries despite their stronger integration into the international system exhibit higher SO2 emissions indicating lower environmental quality than autocratic countries.
Keywords: 330